Laminar thermal-hydraulic efficiency of polyacrylamide solution in double pipe heat exchanger. (April 2019) - Tiong, A N T; Kumar, P; Saptoro, A
Abstract: This paper discusses the thermal-hydraulic efficiency of polyacrylamide (PAA) solution in a double pipe heat exchanger. This study focuses on the laminar regime, with the Reynolds number range from 250 to 2000. This research is carried out numerically through using the ANSYS Fluent software version 15.0. The overall heat transfer coefficient of PAA solution is found to be three times larger than that of water with the concentration of merely 10 ppm. This heat transfer augmentation is attributed to the purely viscous shear-thinning characteristic of the solution. However, the maximum pressure drop of the PAA solution is approximately 31.7 times greater than the value of water. The increased viscosity of the solution is the main contributor of the pressure drop increment. The pressure drop can be reduced by increasing the PAA inlet temperature. As a result of the high pressure drop of the PAA solution, its thermal-hydraulic efficiency is not as good as compared to that of water, particularly at generalized Reynolds number smaller than 1500. The flow of PAA solution is observed to have its best efficiency at the concentration of 10 ppm, generalized Reynolds number of 2000 and PAA inlet temperature of 313.15 K. The best performance index obtained is approximately 1.108.